To What Extent Are Savings–Cash Flow Sensitivities Informative to Test for Capital Market Imperfections? - Tsoukalas, John D.; Tsoukas, Serafeim; Guariglia, Alessandra (Review of Finance, 2017)
We construct a simple model with lumpy investment, cash accumulation, and costly external finance. Based on this model, we propose a new savings specification aimed at examining savings behavior in the presence of investment lumpiness and financial constraints. We then test a key prediction of our model, namely that under costly external finance, savings–cash flow sensitivities vary significantly by investment regime. We make use of a panel of firms from transition and developed economies to estimate the new savings regression which controls for investment spikes and periods of inactivity. Our findings confirm the validity of the model’s prediction.